2015
DOI: 10.1007/s11920-015-0602-0
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the Potential of Mobile Mental Health: New Methods for New Data in Psychiatry

Abstract: Smartphones are now ubiquitous and can be harnessed to offer psychiatry a wealth of real-time data regarding patient behavior, self-reported symptoms, and even physiology. The data collected from smartphones meet the three criteria of big data: velocity, volume, and variety. Although these data have tremendous potential, transforming them into clinically valid and useful information requires using new tools and methods as a part of assessment in psychiatry. In this paper, we introduce and explore numerous anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 48 publications
(53 reference statements)
2
122
0
1
Order By: Relevance
“…Examples of these innovations include using “passive” (i.e., no user input required) data collected from built-in smartphone sensors to predict elevated depressive symptoms and to suggest interventions; 22,23 differentiating depressive versus manic mood states from speech patterns detected from phone conversations; 24 predicting depressive symptoms from Facebook activity; 25 delivering CBT interventions via videogame format; 26 and using smartphone-based mental health apps to treat depression and anxiety. 2729 …”
Section: Icbt Programs For Depressionmentioning
confidence: 99%
“…Examples of these innovations include using “passive” (i.e., no user input required) data collected from built-in smartphone sensors to predict elevated depressive symptoms and to suggest interventions; 22,23 differentiating depressive versus manic mood states from speech patterns detected from phone conversations; 24 predicting depressive symptoms from Facebook activity; 25 delivering CBT interventions via videogame format; 26 and using smartphone-based mental health apps to treat depression and anxiety. 2729 …”
Section: Icbt Programs For Depressionmentioning
confidence: 99%
“…Studies have concluded that smartphone applications can be beneficial in monitoring and evaluating patients [23][24][25], as well as increasing adherence to medical interventions [26,27]. The BUS approach offers the ability to take these studies further in understanding real-time use and overall time spent on apps as a factor that could contribute to health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The communication patterns and the frequency of communication with others of individuals, and their content and manner of speech are also the key signs of several psychiatric disorders [33].…”
Section: Mental Healthmentioning
confidence: 99%